The need for competent work ready English language learners - Ezihaslinda, Ngah; Noor Raha, Mohd Radzuan; Wan Jumani, Fauzi; Noor Azlinda, Zainal Abidin (Elsevier Ltd., 2011)
In Malaysia, Malaysian University English Test (MUET) is a test of English language proficiency used in Malaysian public higher educational institutions for the purpose of undergraduates’ admission. However, in preparing students for the workplace, proficiency test alone is not enough. They also need to be competent in applying the four language skills in work related tasks which cover listening, speaking, reading and writing. Therefore, the aim of this paper is to share the authors’ experience in using thematic approach in developing English proficiency test paper at a technical university in the east coast of Malaysia. The test paper developed encompasses four language skills which share a similar theme. The input from listening and reading texts will be used as the output in speaking (in the form of presentation) and writing assessment. Should this assessment be successful to measure our engineering students’ ability to apply the four skills in work related tasks, this test will show how successful the students are in applying what they have learnt throughout their course of studies at the university. The industries may as well benefit from the assessment as not only it could serve as an indicator to gauge the English language proficiency level of newly-employed staff but also as an instrument to measure their competency on work-related skills where English is concerned. It also holds a potential to be used as an entrance requirement for new employees.